2013
DOI: 10.1021/ic400158q
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Bistability around Room Temperature in an Unprecedented One-Dimensional Coordination Magnetic Polymer

Abstract: The synthesis, crystal structure, and physical properties of an unprecedented one-dimensional (1D) coordination polymer containing [Fe2(S2C6H2Cl2)4](2-) entities bridged by dicationic [K2(μ-H2O)2(THF)4](2+) units are described. The magnetic properties show that the title compound presents pairwise Fe-Fe antiferromagnetic interactions that can be well reproduced with a S = 1/2 dimer model with an exchange coupling, J = -23 cm(-1). The electrical conductivity measurements show that the title compound is a semico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
30
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 11 publications
(35 citation statements)
references
References 71 publications
(65 reference statements)
5
30
0
Order By: Relevance
“…Some of these compounds indicate that the sulfur donor atoms of the [Cu(SC 6 H 2 Cl 2 S) 2 ]entity and even the chloro substituents are able to anchor additional metal centres, specially softer ones, promoting a further polymerization. The electrical studies carried out in this work with 3 and 4 CPs as compare with those previously reported for related CPs based on metal-dithiolene entities bridged by alkali complexes, 20,[35][36][37] suggest that the electrical conductivity is limited to relatively low values, 10 -6 -10 -9 σ•cm -1 , probably because of the limitation in electric current passes through the group 1 metal complexes. These results indicate that the formation of electrically conductive of CPs based on metaldithiolene entities require more efficient connectors.…”
Section: Methodssupporting
confidence: 78%
See 1 more Smart Citation
“…Some of these compounds indicate that the sulfur donor atoms of the [Cu(SC 6 H 2 Cl 2 S) 2 ]entity and even the chloro substituents are able to anchor additional metal centres, specially softer ones, promoting a further polymerization. The electrical studies carried out in this work with 3 and 4 CPs as compare with those previously reported for related CPs based on metal-dithiolene entities bridged by alkali complexes, 20,[35][36][37] suggest that the electrical conductivity is limited to relatively low values, 10 -6 -10 -9 σ•cm -1 , probably because of the limitation in electric current passes through the group 1 metal complexes. These results indicate that the formation of electrically conductive of CPs based on metaldithiolene entities require more efficient connectors.…”
Section: Methodssupporting
confidence: 78%
“…These values are in the range to those found for related CPs formed by metal-dithiolene entities bridged by alkali complexes. 20,[35][36][37]…”
Section: Resultsmentioning
confidence: 99%
“…22 However, to the best of our knowledge examples with thf as ligands have only been previously reported by us. [23][24] Thus, we have described the preparation of the monodimensional coordination polymer (1D-CP) {[K 2 (μ-H 2 O) 2 (thf) 4 ][Fe 2 (SC 6 H 2 Cl 2 S) 4 ]} n from the reaction between [Fe 2 (CO) 6 (µ-SC 6 H 2 Cl 2 S)] and K 2 CO 3 in the presence of HSC 6 H 2 Cl 2 SH. 23 This compound represents the first CP containing dithiolene entities bridging by "s" group metal complexes.…”
Section: Introductionmentioning
confidence: 99%
“…[23][24] Thus, we have described the preparation of the monodimensional coordination polymer (1D-CP) {[K 2 (μ-H 2 O) 2 (thf) 4 ][Fe 2 (SC 6 H 2 Cl 2 S) 4 ]} n from the reaction between [Fe 2 (CO) 6 (µ-SC 6 H 2 Cl 2 S)] and K 2 CO 3 in the presence of HSC 6 H 2 Cl 2 SH. 23 This compound represents the first CP containing dithiolene entities bridging by "s" group metal complexes. Remarkable this new material shows interesting electrical properties including two electrical reversible transitions and electrical bi-stability.…”
Section: Introductionmentioning
confidence: 99%
“…In the cationic fragment the iron atom is coordinated to four oxygen atoms of H 2 O molecules and two from the THF ligands yielding to a distorted octahedral geometry; bond distances and angles (see range 46 On the other hand, geometrical parameters found for the dianionic moiety [Fe 2 (SC 6 H 2 Cl 2 S) 4 ] 2are very similar to those obtained for complexes 1-3 and other already reported for related compounds. 16,17,47 The crystal packing of 4 does not present significant interactions (Fig. S4).…”
Section: Resultsmentioning
confidence: 98%